2008
DOI: 10.1002/j.2168-9830.2008.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Engineering Undergraduate Work Experience: Factoring in Pre‐work Academic Performance

Abstract: This paper examines how undergraduate work experiences affect engineering graduates' post-graduation starting salary, their cumulative grade point average upon graduation, and their likelihood of receiving a job offer prior to graduation. This study contributes to the field of undergraduate work experiences uniquely by taking into account academic performance prior to work experience, including the exact number of work experiences, and examining how gender interacts with work experience to affect the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…One study finds that co-op completers earn a higher salary after graduation, while those who started but did not finish the program earn the same amount as their non-participant peers 5 . These effects hold even when taking gender, major, and prior GPA into account 8 .…”
Section: Career Benefitsmentioning
confidence: 94%
See 2 more Smart Citations
“…One study finds that co-op completers earn a higher salary after graduation, while those who started but did not finish the program earn the same amount as their non-participant peers 5 . These effects hold even when taking gender, major, and prior GPA into account 8 .…”
Section: Career Benefitsmentioning
confidence: 94%
“…While studies have examined the academic and employment outcomes of co-op participation 5,7 , few researchers have accounted for prior academic variables in their analyses 8 . This study aims to narrow the gap between co-op outcomes and prior experiences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Schuurman, Pangborn, and McClintic examined how undergraduate work experience affected engineering students' academic achievement and career development. 30 A total of 1,479 senior engineering students participated in the survey. The results revealed that the students with more working experiences had a higher starting salary after graduation and were more likely to get a job offer prior to graduation.…”
Section: Living Learning Community (Llc)mentioning
confidence: 99%
“…(institutional identity), (2) coops and internships (self-identification through exposure to the norms and values held by professional engineers), and (3) communities of practice (recognition by other in-group members as a professional in the field) 12,13 . Co-ops and internships contribute to students' desire to become an engineer 14 , retention and work self-efficacy 15 , and higher starting salaries and the potential for a job offer by graduation 16 . However, "lack-of-belonging" has been found to be a predictor of switching out of engineering to a nontechnical major 17 , alienating disadvantaged students 18 and even high achieving students 19 from the engineering community.…”
Section: Literature Reviewmentioning
confidence: 99%